Identifikasi Karakteristik Sifat Fisik dan Ciri Morfologi Tanah Gambut pada Penggunaan Lahan Hutan dan Perkebunan di Kecamatan Petasia Timur, Kabupaten Morowali Utara: Identification of Physical and Morphological Characteristics of Peat Soil in Forest and Plantation Land Use in Petasia Timur District, North Morowali Regency - Dea Aurelia Pantilen; Muh. Nathan (Jurnal Ecosolum, 2026)
Forest conversion into plantations drastically alters the physical properties of peat soil. Therefore, this study was conducted to identify and compare the morphological characteristics and physical properties of peat soil under forest and plantation land use in Petasia Timur District, North Morowali Regency. Observation sites were selected using purposive sampling, where T1 and T2 were located in plantation areas, while T3 was situated in a forest area. A comparative analytical method was employed to examine the physical soil properties between peat oil palm plantations and peat forests. The observed parameters included decomposition degree, soil color, bulk density, porosity, and permeability. The deepest peat thickness was found at T2 (550 cm), while the shallowest was at T3 (180 cm). T3 (forest) exhibited a less decomposed or fibric-dominated state with fiber contents of 6.0–8.0 mm, whereas T2 was more decomposed, showing sapric dominance in the first and second layers with fiber contents of 1.0–8.0 mm. The highest permeability was observed in T3 (range 13.4–15.3), and the lowest was in T2 (range 6.7–7.3). The highest bulk density values were recorded at T2 (0.18–0.23 g/cm³), while the lowest were at T3 (0.10–0.15 g/cm³). The highest porosity was found in T3 (86%–89%), and the lowest in T2 (76%–79%). Forest conversion to plantations significantly affects physical soil properties, where permeability and porosity tend to be higher in peat forests compared to oil palm plantations, whereas bulk density shows the opposite trend. Furthermore, forest conversion on peatland also influences morphological characteristics such as soil color, degree of decomposition, and water table levels.